Ta över en verksamhet och få ett kollektivavtal på köpet – Gällande rätt och tillämpligheten av reglerna i 28 § MBL - Ståleker,Noah (2025)
This thesis examines two central questions concerning business transfers under Swedish and EU labour law: (1) which collective agreement, and which parts of it, become binding for the transferee when a business, undertaking, or part thereof is transferred in accordance with Section 6 b of the Swedish Employment Protection Act (LAS); and (2) what role the collective agreement plays in determining which terms and conditions of employment are protected under the EU Transfers of Undertakings Directive. Using a legal dogmatic method, the thesis analyses how binding effect arises from collective agreements under Section 28 of the Swedish Employment (Co-Determination in the Workplace) Act (MBL), and to what extent provisions in collective agreements are transferred to the transferee. Case law from the Swedish Labour Court, and from the Court of Justice of the European Union (CJEU) is examined, alongside legislative materials and academic literature. The thesis concludes that only the normative provisions of a collective agreement – i.e. those directly regulating employment conditions – are transferred under Section 28 MBL. Provisions regulating relations between collective bargaining parties are not included. Notably, the pension exemption found in Section 6 b LAS does not apply to Section 28 MBL, implying that collectively agreed pension benefits also transfer to the transferee. Furthermore, the thesis explores how collective agreements may influence individual employment contracts via incorporation clauses, and the legal implications of dynamic versus static references. The balance between employees’ acquired rights and the transferee’s fundamental rights, including freedom of contract and freedom to conduct a business under the EU Charter of Fundamental Rights, is also analysed in light of relevant CJEU jurisprudence.
Keywords: Arbetsrätt; LAS; MBL; 28 § MBL; 6 b § LAS; Verksamhetsövergång; Överlåtelsedirektivet; övergång av verksamhet